PENGARUH KEPUASAN KARYAWAN TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (SURVAI PADA PERGURUAN TINGGI SWASTA DI WILAYAH JAKARTA BARAT) - Budi Hartono Kusuma; Lina Lina (Jurnal Manajemen Maranatha, 2018)
The aim of this study is to provide empirical evidence of the positive influence of employee satisfaction on employee performance. Employee commitment as intervening variable also wants to be proven through this research. The data used is primary data. Data were obtained through questionnaires distributed to respondents. The respondents were chosen by using purposive sampling method based on certain criteria. The criteria set are as follows: full-time lecturer or homebase lecturer at private universities in West Jakarta area. Hypothesis test uses regression analysis and path analysis. The results showed that employee satisfaction has a positive influence on employee performance. Employee commitment as intervening variable can not be proven through this research.Â Keywords: Employee Commitment; Employee Performance; Employee Satisfaction.